(Invited) Nanomaterials and Anticancer Therapies in-Vitro Studies Using Lab-on-a-Chip Microsystems - Ilona Grabowska-Jadach; Sandra Skorupska; Marcin Drozd; Dominika Kulpinska; Mariusz Pietrzak; Artur Dybko; Zbigniew Brzozka (ECS Meeting Abstracts, 2020)
Introduction Nanomaterials due to their physicochemical properties arouse interest of researchers representing various fields of science, including chemical, biological and clinical analysis. Research in these areas has led to a foundation of nanomedicine, in case of which, both diagnosis and therapy of various diseases are based on nanoparticles (e.g. treatment of infectious or cardiovascular diseases and cancer) [1-3]. Nanoparticles made of biodegradable polymers and lipids, gold- and silver-based nanoparticles, carbon nanotubes, semiconductor-based nanoparticles and many others allow the delivery of therapeutic compounds directly to diseased/altered cells. Lab-on-a-chips for cell cultures studies Lab-on-a-chip microsystems are valuable analytical tools that can be used during both in vitro tests of nanomaterials and development of new therapeutic procedures [4]. Lab-on-a-chip systems enable to precisely control the cells’ microenvironment and overcome the limitations of traditional cell culture methods. In microfluidic systems, a transport of necessary substances (oxygen and nutrients) in appropriate concentrations is ensured. In addition, a flow of a culture medium generates shear stresses, the presence of which affects the functioning of cells and can significantly change the diffusion kinetics and interactions of nanomaterials with a cell membrane. By using the microchannel system, it is possible to obtain concentration gradients of the tested compounds, which better mimic conditions found in living organisms. In such systems, the channels and chambers are characterized by a high surface area to volume (SAV) ratio, which reflects the in vivo conditions (gas diffusion, nutrient transport). The consequence of all the mentioned parameters of microsystems is that we can observe phenomena, which do not occur in the macroscale. Method The microsystems that we used during in vitro studies were made of polymer or polymer and glass. The application of biocompatible and transparent materials for microsystems fabrication allows microscopic observation during tests. Microchambers and microchanels in polydimethylsiloxane (PDMS) were obtained using photolithography and molding method. Both elements (PDMS/PDMS or PDMS/glass) of microsystems were permanently bonded after the use of oxygen plasma. Cell culture in the form of a monolayer (2D model) was obtained when a hybrid system was used, while spherical aggregates (3D model) were obtained using a system made of PDMS. Results and Conclusions In our studies, microsystems were used to assess the cytotoxicity of nanomaterials and test the effectiveness of therapeutic procedures. Biological activity of quantum dots was evaluated and their accumulation inside the cells was monitored. It should be underlined, that the application of microsystems made possible to perform and evaluate the effectiveness of two different therapeutic procedures: electrochemotherapy (ECT) and photothermal therapy (PTT). ECT studies were conducted on a cell monolayer (the most commonly used model in biological studies) in a microsystem with integrated electrodes whereas, the PTT studies were conducted on spheroids (model of the early stage of an avascular tumor). References [1] K. Savitsky, X. Yu, Combined strategies for tumor immunotherapy with nanoparticles, Clin Transl Oncol 21 (2019) 1441-1449. doi.org/10.1007/s12094-019-02081-3 [2] J. Xu, W. Han, T. Jia, S. Dong, H. Bi, D. Yang, F. He, Y. Dai, S. Gai, P. Yang, Bioresponsive upconversion nanostructure for combinatorial bioimaging and chemo-photothermal synergistic therapy, Chemical Engineering Journal 342 (2018) 446-457. doi.org/10.1016/j.cej.2018.02.109 [3] C.K.W. Chan, L. Zhang, C.K Cheng, H. Yang, Y. Huang, X.Y. Tian, C.H.J. Choi, Recent Advances in Managing Atherosclerosis via Nanomedicine, Small 14 (2018) 1702793. doi: 0.1002/smll.201702793 [4] D. Kalinowska, I. Grabowska-Jadach, M. Liwińska, M. Drozd, M. Pietrzak, A. Dybko, Z. Brzózka, Studies on effectiveness of PTT on 3D tumor model under microfluidic conditions using aptamer-modified nanoshells, Biosens Bioelectron 126 (2018) 214-221. doi.org/10.1016/j.bios.2018.10.069